Female CEO and Market Reaction - Ani Mahrita; Agus Setiawan (Jurnal Studi Manajemen dan Bisnis, 2021)
This study aims to examine market reaction to the announcement of female CEOs appointment at companies listed on the Indonesia Stock Exchange (IDX) over the period 2010-2018. The first test uses event study analysis through t-tests using the one-sample t-test method. It was found that the market reacts negatively to the announcement of the appointment of a female CEO. Moreover, further tests are carried out to determine the factors which influenced the negative reactions, such as the characteristics of the female CEOs themselves coupled with the characteristics of the company as the control variable. The results of the regression analysis show that the characteristics of female CEOs in the form of family relations with the board of commissioners have a negative effect on market reaction. While other characteristics such as age and education of the female CEOs do not affect the market reaction. Other additional information shows that company size also has a negative effect to market reaction. Things that need to be considered by companies when they want to appoint a woman as CEO is if the candidate for CEO has a family relationship with the board of commissioners. The size of the company also needs to be considered. The bigger the size of the company, the presence of a female CEO is also increasingly in doubt because it is considered to interfere with the company's existing operations and strategy.